The risk factors profile of coronary heart disease in dyslipidemic patients : Results from a survey in 13 cities in Indonesia (Medical Journal of Indonesia, 2001)
The incidence of coronary heart disease (CHD) has significantly increased and has been associated to the high mortality rate in Indonesia. One important CHD risk is the abnormal lipid profile or dyslipidemia, but there are other risk factors that has been associated with CHD in Western population. In Indonesia, data on CHD risk factors are very limited and usually only available as hospital-based data. The aim of this study is to analyze the CHD risk profile in the private clinical practice setting and to determine the factors affecting CHD in dyslipidemic patients in Indonesia. This study is a cross-sectional survey which targeted physicians in 13 cities in Indonesia who regularly treat patients with dyslipidemia. The majority of dyslipidemic patients in clinical practice setting was the CHD high-risk group. Age, Iow HDL-C and hypertension were the most common risk factors. The prevalence of the risk factors and the proportion of dyslipidemic patients which belongs to the high risk group were comparable to the result of US (L-TAP) study. (Med J Indones 2001; 10: 42-7) Keywords : Coronary Heart Disease, risk factors, dyslipidemia, clinical practice